PENGARUH KUALITAS PELAYANAN SDM BANK SYARIAH TERHADAP KEPUASAN NASABAH: STUDI PADA BPRS BERKAH RAMADHAN - Hermanto Hermanto (Faculty of Economic and Business, 2013)
The purpose of this study was to observe the effect of the quality of human resource services of Islamic banks on customer satisfaction. The analysis technique used in this study is the multiple linear regression method. Data collection in this study combines the questionnaires and interviews. The sampling technique used in this study is accidental sampling method. The results show that there is a quality of the human resources of Islamic banks have an influence on the level of customer satisfaction either partially or simultaneously. While partially, only guarantees only variable that has a significant effect. This shows that it is necessary to improve the quality of service in the SRB Blessings of Ramadan in improving customer satisfactionDOI: 10.15408/etk.v12i1.1907